Crack path for run-out specimens in fatigue tests: is it belonging to high- or very-high-cycle fatigue regime? (Fracture and Structural Integrity, 2015)
Fatigue tests run-out specimens up to 106 – 5x107 load cycles are used to determine the stress levelnamed “fatigue limit”. Nevertheless, it is not clear what kind of fatigue cracking takes or will take place in thesespecimens. To discuss this problem, fatigue tests of titanium alloy VT3-1 specimens have been performedunder tension with different values of R-ratio and under rotating-bending after various thermo-mechanicaltreatments (tempering, surface hardening and their combinations). Well-known S-N curves in High-Cycle-Fatigue regime have been plotted with run-out specimens usually used for “fatigue limit” determination. Then,after fatigue tests, run-out specimens have been tensed up to their failure, and fracture surface analyses havebeen performed for all tested specimens. It is found that run-out specimens in all combinations of treatments,for different R-ratio, have fracture surfaces for crack path in Very-High-Cycle-Fatigue regime. Based on thisresult, all S-N curves have been reconstructed in duplex curves for High- and Very-High-Cycle-Fatigue regimewithout using knowledge about “fatigue limit”. Detailed fracture surfaces analyses have been developed, andcrack paths have been compared for various combinations of materials and surface states.
Keywords: Fatigue limit